2003
DOI: 10.1073/pnas.0437938100
|View full text |Cite
|
Sign up to set email alerts
|

Communication between neocortex and hippocampus during sleep in rodents

Abstract: Both neocortical and hippocampal networks organize the firing patterns of their neurons by prominent oscillations during sleep, but the functional role of these rhythms is not well understood. Here, we show a robust correlation of neuronal discharges between the somatosensory cortex and hippocampus on both slow and fine time scales in the mouse and rat. Neuronal bursts in deep cortical layers, associated with sleep spindles and delta waves͞ slow rhythm, effectively triggered hippocampal discharges related to f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

73
787
4
5

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 838 publications
(869 citation statements)
references
References 44 publications
73
787
4
5
Order By: Relevance
“…Slow oscillation was soon shown also in the human EEG during sleep (Achermann and Borbely, 1997;Amzica and Steriade, 1997;Molle et al, 2002), indicating its crucial importance for neocortical function. An important aspect of slow oscillation is its ability to temporally organize other cortical patterns, such as sleep spindles, gamma oscillations and K complexes (Achermann and Borbely, 1997;Amzica and Steriade, 1997;Molle et al, 2002;Steriade and Amzica, 1998a;Mukovski et al, 2006) and hippocampal sharp wave ripples (Sirota et al, 2003).…”
Section: Slow (<1 Hz) Rhythms-mirceamentioning
confidence: 99%
“…Slow oscillation was soon shown also in the human EEG during sleep (Achermann and Borbely, 1997;Amzica and Steriade, 1997;Molle et al, 2002), indicating its crucial importance for neocortical function. An important aspect of slow oscillation is its ability to temporally organize other cortical patterns, such as sleep spindles, gamma oscillations and K complexes (Achermann and Borbely, 1997;Amzica and Steriade, 1997;Molle et al, 2002;Steriade and Amzica, 1998a;Mukovski et al, 2006) and hippocampal sharp wave ripples (Sirota et al, 2003).…”
Section: Slow (<1 Hz) Rhythms-mirceamentioning
confidence: 99%
“…Tamminen et al (2010Tamminen et al ( , 2013 showed that this integration was associated with sleep spindle activity. This suggests that sleep-associated neural replay may be involved in lexical integration, given that sleep spindles are temporally correlated with the occurrence of hippocampal ripples (Siapas & Wilson, 1998;Sirota et al, 2003), which reflect hippocampal replay of newly acquired memories (Girardeau et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence suggests that the neuronal interaction between hippocampus and neocortex also plays an important role in memory formation (Jutras et al, 2009;Sirota et al, 2003) and memory functions degrade after damage to the hippocampus (Manns et al, 2003;Zola et al, 2000). Interestingly, we found that the left and right temporal lobes turn out to be the driving forces for the highfrequency overconnectivity in older age, which is directly related to cognitive decline.…”
mentioning
confidence: 58%